2008
DOI: 10.1080/08039480801985146
|View full text |Cite
|
Sign up to set email alerts
|

The Neuropsychiatric Inventory—NPI. Validation of the Danish version

Abstract: Assessment of neuropsychiatric symptoms in dementia has great clinical importance. The aim of the study was validation of the Danish version of the NPI, using assessments of 72 demented and 29 non-demented of age 65+ years and their caregivers at three visits. The NPI was administered by the same psychiatric nurse interviewing the same caregiver. At visits 1 and 3, a psychogeriatrician assessed the participant using the ICD-10, the Geriatric Deterioration Scale (GDS) and the Clinical Global Impression (CGI) as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
8
0
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 9 publications
2
8
0
2
Order By: Relevance
“…As in the original study [24], the same NPI domains (except for anxiety) were negatively correlated with MMSE. Moreover, a positive correlation between depression/dysphoria NPI domain and a depression assessment instrument (in the present study, the GDS) was also found in other previous studies [24, 49]. …”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…As in the original study [24], the same NPI domains (except for anxiety) were negatively correlated with MMSE. Moreover, a positive correlation between depression/dysphoria NPI domain and a depression assessment instrument (in the present study, the GDS) was also found in other previous studies [24, 49]. …”
Section: Discussionsupporting
confidence: 91%
“…The psychometric proprieties of the European Portuguese version of NPI seem to be in accordance with the original studies [24, 30], as well as with other previous international validation studies [39-44, 49-51]. …”
Section: Discussionsupporting
confidence: 88%
“…The caregiver rates each symptom according to the frequency and severity. The Danish validated version is used [45]. The score (frequency times severity) for all items in total, as well as subitems (depression, anxiety, aggression, irritability and apathy) will be used.…”
Section: Methodsmentioning
confidence: 99%
“…Dementia and psychiatric disorders are the most frequent risk factors. Since 1994, Neuro Psychiatric Inventory for Nursing Homes (NPI-NH) is used for patients with dementia (Cummings et al, 1994) or without dementia (Korner et al, 2008;Squelard et al, 2012), and sometimes with psychiatric diagnosis (Baranzini et al, 2013;Iverson et al, 2002). For these older adults, professionals would need advice and support (Droes et al, 2005) regarding appropriate medical or psychosocial interventions (Van Mierlo et al, 2010).…”
Section: Introductionmentioning
confidence: 99%